Krait envenomation in Thailand - Achara Tongpoo (2019)
© 2018 Tongpoo et al. Purpose: Three species in the genus Bungarus inhabit Thailand. Among these, Bungarus candidus (Malayan krait) is the most common and deadliest. Currently, the clinical manifestations of patients envenomed by kraits, especially Bungarus fasciatus (banded krait), have not been thoroughly investigated. This study was performed to elucidate the clinical manifestations and outcomes of patients bitten by kraits in Thailand. Materials and methods: The data of krait envenomation cases that occurred during a 9-year period were obtained from the Ramathibodi Poison Center Toxic Exposure Surveillance System and retrospectively analyzed. Results: In total, 78 cases of krait envenomation were included. Most patients were male (59.0%) and the median age was 28 years. All had minimal local effects. The median duration from the bite to the onset of neurological manifestations was 3 hours (range, 0.5–8 hours). Besides neurological effects, the patients also developed high blood pressure (67.4%), tachycardia (61.7%), hypokalemia (55.3%), and hyponatremia (17.6%). Severe hyponatremia (<120 mEq/L) was noted in four pediatric patients. Other clinical manifestations were bradycardia, abdominal pain, and rhabdomyolysis. The mortality rate was 6.4%, and all deaths occurred from B. candidus bites. Eighty-six percent of patients received antivenom. Most patients (75.6%) were intubated and underwent assisted ventilation for a median of 6 days (range, 1–37 days). The median length of hospital stay was 7 days. Some patients developed complications during hospitalization; the most common was pneumonia. These in-hospital complications were significantly associated with death. Conclusion: Although krait bites caused only minimal local effects, the mortality rate was still high, particularly from Malayan krait bites. Besides neurological effects, other clinical manifestations were high blood pressure, tachycardia, hypokalemia, and hyponatremia. Thus, vital signs and electrolytes should be frequently and closely monitored in these patients. Apart from antivenom treatment, adequate supportive care including management of complications might help to decrease the mortality rate.